Can new consumption promote urban industrial resilience? Empirical evidence from pilot cities of information consumption - Chao Han; Hang Su (PLoS ONE, 2025)
The rapid advancement of digital technology and its widespread application have led to digitalization, personalization, and customization in the demand side of China’s economy. Enhancing industrial resilience through new types of consumption is of great practical significance for expanding domestic demand and promoting high-quality, sustainable economic growth in China. This study examines the impact of the Information Consumption Pilot City (ICPC) policy as a quasi-natural experiment on urban industrial resilience, employing the difference-in-difference (DID) method for empirical analysis. The findings reveal that the ICPC policy significantly enhances the level of urban industrial resilience. Heterogeneity tests indicate that this enhancement effect is particularly pronounced in eastern, central, and larger urban regions. Furthermore, the ICPC policy primarily strengthens urban industrial resilience through three mechanisms: information development, entrepreneurial agglomeration, and digital financial effects. This study contributes to the literature on new consumption and urban industrial resilience in the digital economy, evaluates the economic impacts of pilot policies on information consumption, and offers valuable implications for policymakers.